UPAYA PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP MELALUI MODEL INVESTIGASI KELOMPOK - Fahradina, Nova; Mawardati, Risy (Al-Khawarizmi, 2019)
One of the objectives of mathematics learning is to learn to communicate, because through communication students can communicate ideas, reasoning, and be able to compile mathematical evidence using complete sentences, symbols, tables, diagrams, or other media. One learning model that can be applied to improve students' mathematical communication skills is a group investigation model. This study aims to determine the improvement of students' mathematical communication skills between students who obtain group investigative learning and students who obtain conventional learning are reviewed as a whole and based on the level of students. This study uses experimental research. The design of this study was a pre-test post-test control group design. The population in this study were all seventh grade students of SMP Negeri 9 Banda Aceh. Samples are taken through random sampling techniques. To obtain research data, the instrument is used in the form of tests of students' mathematical communication skills. The results of the study showed that the mathematical communication skills of students who received group investigation learning were better than students who obtained conventional learning both overall and based on the level of students.